TOXOPLASMOSIS: VETERINARY HYGIENIST AND RISK COMMUNICATION - C. Disanto; F. Alberti; F. Fasano; G. V. Celano (Italian Journal of Food Safety, 2011)
Toxoplasmosis is a worldwide protozoarian pathology, caused by Toxoplasma gondii. Toxoplasmosis is a human pathology with an high risk of diffusion because the parasite can be present in many food and sometimes it is very hard to demonstrate a direct relation between clinical cases and food consumption. The aim of this work was to assess toxoplasmosis risk communication performed by veterinary hygienists involved in local health authority (ASL). The results demonstrate that informative campaigns should be organized to show toxoplasmosis risk communication and to organize educational nutrition programs by veterinarians regarding risks caused by animals or parasitized food consumption.